2010
DOI: 10.1007/s10165-010-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of musculoskeletal ultrasound in Japan: a survey of practicing rheumatologists

Abstract: We aimed to describe how often Japanese rheumatologists currently use musculoskeletal ultrasound (MSUS), and how they are currently being trained in the use of this imaging technique. Questionnaires were sent to 200 Japanese rheumatologists: 100 to participants attending the first Scientific Meeting of the Japanese Society of Imaging in Rheumatic Diseases in 2006, and 100 to other randomly selected rheumatologists certified by the Japan College of Rheumatology. A total of 139 questionnaires (74 from meeting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…While a solid and still growing body of evidence supports its use in daily rheumatologic practice, operator dependency and the long learning curve represent the main limitations. To date, different teaching approaches have been proposed and different training experiences have been described (), but the best method for allowing rheumatologists to obtain and maintain competency in musculoskeletal US has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…While a solid and still growing body of evidence supports its use in daily rheumatologic practice, operator dependency and the long learning curve represent the main limitations. To date, different teaching approaches have been proposed and different training experiences have been described (), but the best method for allowing rheumatologists to obtain and maintain competency in musculoskeletal US has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Many surveys found that the lack of training was the major concern hampering the spread of MSUS among rheumatologists [15,16,27]. In fact, Maasa et al found that the development of training courses and informal training have doubled the number of MSUS users in Japan over 3 years [28].…”
Section: Discussionmentioning
confidence: 99%
“…The main indications were as follows: rheumatoid arthritis,shoulder pain, peripheral spondyloarthritis, ankle pain and guidance of interventional procedures. MSUS was used for procedures guidance by 47.2% of respondents, more frequently than European and Japanese rheumatologists [12,16,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations